Peran Kepala Sekolah Dalam Membentuk Kedisiplinan Siswa Di Mts Al - Washliyah Km.6 Medan - Bintang Ridzky Dwi Putra; Muhammad Rifai (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE ROLE OF THE PRINCIPAL IN SHAPING STUDENT DISCIPLINE AT MTS AL - WASHLIYAH KM.6 MEDAN This research analyzes the significance of the managerial role of madrasah heads in transforming student discipline culture thru an integrative preventive and corrective approach. Thru the design of disciplinary codification policies, the strengthening of Islamic values, habituation conditioning thru regular assemblies, and direct role modeling articulation, the head of the madrasah acts as the primary determinant in enforcing institutional behavioral order. The implementation of this strategy is collectively supported by the active participation of educators, an intensive supervision system during critical hours, and an educational-gradual sanction mechanism that synergizes with Guidance and Counseling (BK) services and parental involvement. Although the effectiveness of this policy has been empirically proven to stimulate a conducive learning environment and increase students' interest in learning, its acceleration is still hindered by internal factors such as low self-motivation among students, as well as external obstacles like the sociocultural influence of peers, minimal structured appreciation (reward system), and the heterogeneity of family economic and educational backgrounds.